Ordinance No. 4, §§ 5 & 10, Leavenworth Town Council (1906) (Leavenworth, Washington). - (:unkn) unknown (General Publisher, 1906)
It shall be unlawful for any person or persons within the corporate limits of said Town, to discharge or cause to be discharged any Pistol, Gun, or other firearm or firearms, loaded with leaden or other misle at any time, under any circumstances, within the corporate limits of said town, excepting officers of the law in the discharge of their duties, or in necessary and urgent defense of person or property. It shall be unlawful for any person or persons within the corporate limits of said town, to carry on or about the person any concealed pistol, revolver, dirk, bowie-knife, billy, slung-shot, metal knuckles, or other dangerous or deadly weapon or weapons of any kind, excepting only officers of the law in the discharge of their duties; and any person or persons so offending shall be deemed guilty of a misdemeanor, and upon conviction thereof shall be subject to the penalty hereinafter provided."
--
Keywords: DISCHARGE